The Influence of the University Education of the Public Accountant on the Efficiency of the Administration of Public Resources - Castro De la Cruz, Josseline Aidee; Vázquez Ramos, Candelaria (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To evaluate whether future Public Accountants have fundamental knowledge about the relevance of government auditing in the administration of public resources; it also aims to highlight the importance of this process in an efficient and transparent administration, and its potential to contribute to fight corruption in the government field.MATERIAL AND METHOD: A quantitative approach with a descriptive scope was implemented, using documentary and field techniques, the surveys were applied to a sample population of 100 students of the Public Accounting Degree of a Mexican public university.RESULTS: Out of the research, it stands out that 72% of those who were surveyed do know what auditing is, 88% know how to recognize the basic definition, 62% consider it as very important, and 73% believe that it is essential to mitigate corruption.CONCLUSIONS: The government audit through inspection, sets the standard in the administration of public resources, to demonstrate that it must be carried out in a diligent manner, making it clear that any act of fraud or case of corruption can be detected and punished.
Keywords: Professional education; Government audit; Transparency; Inspection; Public resources.